Pengaruh Beban Kerja, Disiplin Kerja, dan Konflik Kerja terhadap Kinerja Karyawan PT. Barata Indonesia (Persero) Divisi Sumber Daya Air Tegal - Fadhilah, Diamantina Shafir; Tabrani; Murdiati, Sri (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
This study seeks to examine the impact of Workload, Work Discipline, and Work Conflict on Employee Performance at PT. Barata Indonesia (Persero) Tegal Water Resources Division. This research employs a quantitative methodology including a sample of 51 non-production employees. The employed data analysis technique is descriptive statistics, utilising the method of successive intervals with the assistance of the SPSS 22 application. This study use multiple linear regression analysis as its analytical tool. The findings indicate that workload, work discipline, and work conflict each exert a positive and substantial influence on performance. All four independent factors concurrently exert a considerable influence on employee performance.